Hydrological Analysis of Mini Hydro Power Plants (PLTM) Using The Flow Duration Curve Approach - Nengah Bennuwardana; Sukendra Martha; Yosef Prihanto; Dangan Waluyo; Firmansyah Firmansyah; Bachtiar Rifai (CV RIFAINSTITUT, 2025)
Hydrological analysis is crucial in the planning of a Mini-Hydro Power Plant (PLTM). This study aims to examine the hydrological aspects of the Way Besai PLTM, located in Bonglai Village, Way Kanan Regency, Lampung Province. The Way Besai Mini-Hydro Power Plant (PLTM) is a runoff-river PLTM scheme located approximately 242 km north of Bandar Lampung City, Lampung Province, Indonesia. The data used include daily rainfall data from six rainfall stations, climate element data from the Radin Inten II Meteorological Station, and outflow data from the Besai PLTA. The rainfall data were analyzed for consistency using the Mass Curve method, with only three stations deemed consistent. Potential evapotranspiration was calculated using the Modified Penman method. Furthermore, the rainfall data were converted into daily discharge data using the F.J. Mock Rainfall to Runoff hydrological method. The catchment area is 449.14 km2 at the intake site and the average annual rainfall reaches 2,366 mm/year. The analysis results are used to determine the mainstay discharge (plant discharge) and the planned flood discharge through the Flow Duration Curve (FDC). Based on these results, the Way Besai Hydroelectric Power Plant is projected to have a generated power of 9.2 MW and an annual energy of 67.513 GWh resulting from the utilization of an effective water head of 67.45 m and a maximum plant discharge of 16.5 m3/second.